Iterative reconstruction of detector response of an Anger gamma camera. (7th May 2015) - Morozov, A; Solovov, V; Alves, F; Domingos, V; Martins, R; Neves, F; Chepel, V
Abstract: Statistical event reconstruction techniques can give better results for gamma cameras than the traditional centroid method. However, implementation of such techniques requires detailed knowledge of the photomultiplier tube light-response functions. Here we describe an iterative method which allows one to obtain the response functions from flood irradiation data without imposing strict requirements on the spatial uniformity of the event distribution. A successful application of the method for medical gamma cameras is demonstrated using both simulated and experimental data. An implementation of the iterative reconstruction technique capable of operating in real time is presented. We show that this technique can also be used for monitoring photomultiplier gain variations.